A educação ambiental nos centros de educação infantil e escolas municipais de Três Lagoas, em Mato Grosso do Sul: dialogando com os currículos educacionais em tempo de pandemia - 2019-2023 - Oliveira, Arlinda Montalvao de (2023)
The objective of this doctoral research was to analyze Environmental Education in basic education in the Municipal Education Network of Três Lagoas/MS, based on the Educational Policy provided for in Law 9795/99 and the contributions of Critical Environmental Education. The process of building knowledge and theoretical foundations was based mainly on the pedagogical currents of Sauvé (2005) and the Education perspective of Paulo Freire (1981), thus, Environmental Education starts from the individual's awareness to go through the process of change, which focuses on individual and collective relationships, and in this sense, the individual relates socially. In this way, they are participants with their knowledge, their actions and relationships with the environment, for which they are co-responsible for the positive or negative consequences in their living space; together they go through the process of awareness and transformation. The qualitative methodological basis follows the studies of Minayo (2007). The analysis of the results and the Complementary Pedagogical Learning Activities – APCAs were based on theoretical reflections, reports of experiences, records, preparation and interpretation of maps, graphs and boards illustrating the environmental problems identified in the surroundings of five schools selected for the study. The results of the research were that all five schools surveyed develop themes focused on Environmental Education, which included elements of landscapes, natural resources and environmental issues distinct from the locality. Some information collected through field research allowed us to recognize the reality of the educator, his actions and activities carried out outside and inside the school space; the relationship between the educator and the student; their knowledge and approaches to different environmental issues; living space, socio-environmental crystallization through their posture and attitudes relevant to environmental problems, in the effective teaching-learning process of Environmental Education. A fragmented structure centered on content standardized by areas of school knowledge can be seen, which constitutes one of the unfavorable factors for the consolidation of Environmental Education in municipal public education institutions, which allowed knowledge and reflection on the pedagogical trends adopted in the process of teaching and learning, used to work on environmental issues in these communities and encourage some possibilities for actions for Environmental Education for students and professionals, in formal and non-formal teaching spaces in the municipality studied.